A Brief Review of Hydrogen Production Methods and Their Challenges - Dash, Santanu Kumar; Chakraborty, Suprava; Elangovan, Devaraj (Energies (Basel), 2023)
Hydrogen is emerging as a new energy vector outside of its traditional role and gaining more recognition internationally as a viable fuel route. This review paper offers a crisp analysis of the most recent developments in hydrogen production techniques using conventional and renewable energy sources, in addition to key challenges in the production of Hydrogen. Among the most potential renewable energy sources for hydrogen production are solar and wind. The production of H2 from renewable sources derived from agricultural or other waste streams increases the flexibility and improves the economics of distributed and semi-centralized reforming with little or no net greenhouse gas emissions. Water electrolysis equipment driven by off-grid solar or wind energy can also be employed in remote areas that are away from the grid. Each H2 manufacturing technique has technological challenges. These challenges include feedstock type, conversion efficiency, and the need for the safe integration of H2 production systems with H2 purification and storage technologies.